New development: Corporatization of local authorities in England in the wake of austerity 2010–2016. Issue 6 (19th September 2018) - Ferry, Laurence; Andrews, Rhys; Skelcher, Chris; Wegorowski, Piotr
Abstract: A key institutional driver of current reforms within English local government is 'alternative service delivery'. Our review of councils' annual accounts between 2010/11 and 2016/17 suggests 'corporatization'—the creation of local authority companies—is a growing phenomenon across the whole of English local government. This represents such a significant and far-reaching development in the governance, performance and efficiency of local public services that it constitutes a major field-level change at the interstices of the institutions of state, market, corporation and community. In this article, the authors briefly sketch ways corporatization could be regarded as a field-level change, before presenting findings and reflecting on their implications.